Statistical abstract for East Pakistan : vol. lv - East Pakistan (Pakistan). Bureau of Commercial and Industrial Intelligence; East Pakistan (Pakistan). Provincial Statistical Board (Dacca : Provincial Statistical Board and Bureau of Commercial and Industrial Intelligence, (Planning Dept.), 1958)
"Containing statistical data on various subjects for the years ... to ... (wherever available)."
Description based on: Vol. 3 (1st impression) 1949/50 to 1953/54.
Vol. 3 is a revised and enlarged issue of its second edition. Cf. Preface, vol. 3.
Includes revised editions numbered consecutively with the original issue.
Keywords: Bangladesh -- Statistics -- Periodicals